Trend change in number of medals won at the Olympics and Paralympics games in Serbian athletes - Ivanovic, J. (Serbian Journal of Sports Sciences, 2020)
The main objective of this paper is to analyze and determine the trend change in number of medals won at the Olympics and Paralympics Games from 2008 to 2016 in Serbian athletes. Data from the official website of the Olympics Games (www.olympic.org) were used for the analysis purposes. Data regarding participation and medals won at the Olympics and Paralympics Games in Bejing 2008, London 2012, Rio 2016 were used. The results of the analysis showed that the Serbian athletes achieved a positive increase regarding the number of medals won at the level of almost two (1.67) Olympic and two (2.32) Paralympic medals on average. In addition, the number of female participants at the Olympics Games in 2012 and in 2016 in particular, was increased significantly compared to year 2008. At the previous two Olympics Games (London 2012, Rio 2016) the same number of medals was won 2 medals in both male and female competition, i.e. 4 medals in total. Based on the presented results of the analysis and trend change in the number of medals won in the observed multiannual period, it can be undoubtedly concluded that our athletes are continuously recording a positive trend in winning medals at the Olympics and Paralympics Games.